Ethical Evaluation of Tithes and Offerings in Osun Baptist Conference, Nigeria (2013)
Existing studies on tithes and offerings have focused on the historical dimension of these religious obligations at the neglect of their ethical perspectives which are central to the success of the drive for and voluntary participation in the practice. This study, therefore, examined the tradition of tithes and offerings in the Osun Baptist Conference, in terms of payers, types, objects and disbursement with a view to evaluating their ethical alignment with Biblical injunctions with reference to Leviticus 27:30-32; 1 Chronicles 16:29; Malachi 3:8-10; I Corinthians 16:1-2; and II Corinthians 9: 5-8. The deontological theory served as the theoretical framework for the study. Eighty churches were randomly sampled from the 16 Baptist associations that formed Osun Baptist Conference. A questionnaire was administered to 480 purposively selected members of these churches. In-depth interviews were conducted with 35 purposively sampled Baptist members within the Conference. Five years financial records of 50 churches served as a major source of information. While qualitative data were subjected to content analysis, quantitative data were analysed using descriptive statistics. The tradition of tithes and offerings in Osun Baptist Conference showed that tithes were paid by both salary earners and non-salary earners on Sundays. Offerings were of two categories: general and special offerings. The former were given every Sunday service and during some weekly programmes. The latter were given through special thanksgivings, private pledges or vows. The object tithed was solely monetary while offerings were both monetary and material. A study of five years (2007 – 2011) church records showed that 80% of the revenue and budget of the churches was tied to tithes, while 20% was tied to offerings and donations. Out of the budgeted income for tithes, 65.0% was realised while 26.5% was realised from offerings. The tithing practice of the Osun Baptist Conference agreed partially with the Old Testament injunctions in Leviticus 27:30-32; Malachi 3:8-10. The Old Testament mentioned three tithes: the Levites’, great feasts and poor’s tithes. Only the Levites’ tithe was practised in the Conference; tithing of objects was also completely absent. The offerings of the Conference aligned with both the Old and the New Testaments injunctions, as seen in 1 Chronicles 16:29; 1 Corinthians 16:1-2; 2 Corinthians 9:7. While the Bible prescribed that tithes should be used for evangelism and offerings for all forms of needs, the practice in Osun Baptist Conference conformed partially with these injunctions. Both tithes and offerings were lumped together and disbursed on several needs of the church. However, 80% of our respondents agreed that members should give whatever they have as tithes; 60% agreed that after paying Church workers’ salary from tithes, the rest should be disbursed on evangelism. One hundred percent agreed that every material possession of members should be tithed. The practice of tithes and offerings of Osun Baptist Conference is partially in line with the Biblical injunctions. Therefore, there is need for ethical reorientation of Osun Baptist Conference churches on correct biblical practices in terms of payment of tithes and offerings, and disbursement of same